Autobiografi Atlet Gulat Ayub Bagus Setiawan : Mahasiswa Universitas Negeri Malang, Fakultas Ilmu Keolahragaan, Departemen Pendidikan Jasmani Kesehatan dan Rekreasi Angkatan 2019 Peraih Medali Emas Pomnas di Kalsel Tahun 2023 - Ayub Bagus Setiawan; Siti Nurrochmah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Autobiography of Wrestler Ayub Bagus Setiawan: A Student at Malang State University, Faculty of Sports Science, Department of Physical Education, Health, and Recreation of the 2019 Batch. He won the Gold Medal at the National Student Sports Week (POMNAS) in South Kalimantan in 2023, narrates his life journey from childhood to achieving the highest achievements in wrestling. Ayub was born in Banyuwangi on August 2, 2001, as the second of three siblings. His wrestling career began while attending SMP Negeri 1 Tegaldlimo and continued at SMA Negeri Olahraga Sidoarjo. From a young age, Ayub has loved and devoted himself to wrestling. Motivation, enthusiasm, and support from family and the community have made him more diligent in training. Choosing to continue his education in the Department of Physical Education, Health, and Recreation at the Faculty of Sports Science at Malang State University is a step to deepen his knowledge of sports. Ayub's athletic career reached its peak when he won at POMNAS 2023, a remarkable achievement in his sports career. This autobiography serves as an inspirational record of the dedication, hard work, and spirit of an athlete who has achieved remarkable success in the sport of wrestlings.